2013
DOI: 10.1016/j.jcrs.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-disruption collagen crosslinking for keratoconus: One-year results

Abstract: Corneal epithelial-disruption CXL was safe and effective in medium-term stabilization of keratoconus with an improvement in topographic and refractive parameters and less patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
1
44
1
Order By: Relevance
“…With growing interest in transepithelial CXL, investigators have reported several enhanced techniques such as the use of chemical agents,15 mechanical epithelial disruption16 and iontophoresis17 18 to increase the delivery of riboflavin solution into the corneal stroma through the intact epithelium. However, it is presently unknown whether or not any of these transepithelial techniques are as effective in treating progressive corneal ectasia as the standard epithelium-off technique,19 and there are currently no clinical trials comparing different techniques available.…”
Section: Introductionmentioning
confidence: 99%
“…With growing interest in transepithelial CXL, investigators have reported several enhanced techniques such as the use of chemical agents,15 mechanical epithelial disruption16 and iontophoresis17 18 to increase the delivery of riboflavin solution into the corneal stroma through the intact epithelium. However, it is presently unknown whether or not any of these transepithelial techniques are as effective in treating progressive corneal ectasia as the standard epithelium-off technique,19 and there are currently no clinical trials comparing different techniques available.…”
Section: Introductionmentioning
confidence: 99%
“…The first epithelium-on CXL (epi-on-CXL) protocols included the use of multiple topical applications of tetracaine 1% to disrupt epithelial tight junctions (Boxer Wachler et al., 2010, Chan et al., 2007) and partial epithelial debridement in a grid pattern (Rechichi et al., 2013). More recently, novel formulations of riboflavin have been developed to facilitate epi-on-CXL.…”
Section: Introductionmentioning
confidence: 99%
“…The technique involves disruption of the corneal epithelium using a custom-designed surgical instrument, in place of the complete epithelial debridement performed during conventional CXL. 11 The technique of CXL using epithelial disruption was first developed and introduced in our department in 2007 by Dr Sheraz Daya, and we report our results to date.…”
Section: Introductionmentioning
confidence: 83%
“…10 There seems, therefore, a place for a CXL technique that involves minimal disturbance to the corneal epithelium, but where efficacy and safety are maintained for even the most severe cases of keratoconus. 11 In an attempt to address this, a hybrid technique for CXL has been adopted at The Corneoplastic Unit at Queen Victoria Hospital, East Grinstead (UK). The technique involves disruption of the corneal epithelium using a custom-designed surgical instrument, in place of the complete epithelial debridement performed during conventional CXL.…”
Section: Introductionmentioning
confidence: 99%